2003
DOI: 10.1007/bf03256655
|View full text |Cite
|
Sign up to set email alerts
|

Combination Therapy with Single Inhaler Budesonide/Formoterol Compared with High Dose of Fluticasone Propionate Alone in Patients with Moderate Persistent Asthma

Abstract: Symbicort (budesonide/formoterol in a single inhaler) was more effective than a high dose of fluticasone propionate in improving lung function, reducing use of reliever medication and improving control of moderate persistent asthma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(29 citation statements)
references
References 15 publications
1
28
0
Order By: Relevance
“…Bateman and colleagues 228 reported that patients treated with BUD/FF had a lower incidence of mild asthma exacerbations than patients treated with FP, occurring in 50 patients (29.8%) and 74 patients (42.0%), respectively. Mild exacerbations were defined as awakening due to asthma on two consecutive nights, morning PEF at least 20% below that at baseline on two consecutive days or the need to use at least four inhalations of reliever medication.…”
Section: Exacerbationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bateman and colleagues 228 reported that patients treated with BUD/FF had a lower incidence of mild asthma exacerbations than patients treated with FP, occurring in 50 patients (29.8%) and 74 patients (42.0%), respectively. Mild exacerbations were defined as awakening due to asthma on two consecutive nights, morning PEF at least 20% below that at baseline on two consecutive days or the need to use at least four inhalations of reliever medication.…”
Section: Exacerbationsmentioning
confidence: 99%
“…228 It was a multi-centre study conducted in 37 centres across six countries, involving the recruitment of 373 patients. Only 344 patients were randomised.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies suggest that daily asthma control improves to a greater extent with the addition of a LABA than with a higher ICS dose alone in patients with mild to severe asthma (13)(14)(15)(16). Systematic reviews have found a 12-14% reduction in the risk of an exacerbation with traditional ICS/LABA maintenance therapy plus SABA for relief compared with a higher ICS dose plus SABA in patients with moderate to severe asthma (17,18).…”
Section: The Role Of Ics and Laba In Improving Asthma Controlmentioning
confidence: 99%
“…[54]. Alternative strategies to lower the C o p y r ig h t G e n e r a l P r a c t ic e A ir w a y s G r o u p R e p r o d u c t io n p r o h ib it e d total daily dose of ICS include the addition of longacting bronchodilators or leukotriene modifiers in people with moderate to severe asthma, but not in those patients with mild persistent asthma [55][56][57][58]. Such new agents and new strategies would potentially reduce both the incidence and fear of adverse events due to ICS -an important consideration in achieving patient adherence.…”
Section: Systemic Corticosteroidsmentioning
confidence: 99%